Political Participation and Sustainability: Exploring Contemporary Challenges - Gherghina, Sergiu (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Over the last two decades, the literature on political participation has flourished, reflecting the increasing use of diverse modes of citizen involvement. These include established modes of participation, such as voting, protests, mass demonstrations, and petition signing, but also newer modes specific to the online environment (ICT-related), participation in referendums, public consultations, or engagement in political deliberation. The importance and intensity of these modes is reflected both in the number of people getting involved and in the increasing number of policies that are subject to various modes of participation on a regular basis. There is extensive literature about how these modes of participation function, why people get involved, and the consequences of their participation. However, limited attention is paid to the relationship between political participation and the pursuit of sustainability at a local, regional, or central level. Existing studies indicate that citizen engagement can be a cost-effective method to characterize changes of local environments; however, not much is known beyond this process. This Special Issue aims to address this void in the literature and brings together contributions that analyze how participation can be associated with sustainability and local development in various settings. It explores the relationship between political participation and the management of their local environment. This Special Issue enhances the existing knowledge and understanding about how modes of participation can be reflected in stronger sustainability. The Special Issue provides the space for an academic debate that addresses issues such as climate change, resource allocation, or the pursuit of sustainability programs and policies. The contributions include a mix of single-case studies and comparative analyses across European countries.